Perceptions of the role of Lantana camara on human well-being and rural livelihoods in Vhembe Biosphere Reserve, South Africa - Mhlongo, Edward Swazi (Rhodes University, Faculty of Science, Department of Environmental Science)
In the past, social aspects on biological invasions were less documented, this hindered the development of sound and effective management of Invasive Alien Species (IAS). However, there has been a shift in trends with more studies on biological invasions integrating local knowledge together with ecological studies to develop effective management interventions. Invasive Alien Species are widespread throughout Southern Africa and are usually prevalent in the rural areas. Limpopo province consists of large rural areas where people depend on natural resources, wild and exotic species for their livelihoods. Lantana camara is one of the major invaders that is problematic worldwide having detrimental impacts on biodiversity, ecosystem functions, and economies. This study assessed the perceptions of the role of L. camara on the well-being and rural livelihoods of local communities in the Vhembe Biosphere Reserve using household surveys. A total of 300 surveys were administered in six villages. The study further used a two-pronged approach to examine invasion extent and management options. The two-pronged approach included (i) detailed vegetation surveys in 50 household yards within each village, and (ii) focus group to solicit local knowledge of invasion extent and managing L. camara by the rural communities. The results of the study showed that almost all the respondents knew L. camara and could describe it. Most of the respondents were of the view that L. camara had no negative impacts on their livelihoods. Other respondents stated costs associated with L. camara were more than benefits and wanted a reduction in L. camara densities in the area. Most respondents wanted more government intervention to help in managing L. camara, this is because of the perceived future impacts of L. camara. Vegetation survey results showed no significant difference in L. camara abundances and plant heights among the six study villages. The average number of L. camara counted per household yard in all villages was (2.41 ± 0.20) plants, with average plant basal diameter of (0.94 ± 0.02 cm). There were significant differences in canopy width of L. camara among the six study villages. Plant basal diameter was high in Tshakhuma (1.05 ± 0.04 m) and Duthuni (1.00 ± 0.04 m) villages, and low in Ha Mutsha village (0.82 ± 0.03 m). Lantana camara canopy width at household level across all villages averaged 1.34 ± 0.03 m. Canopy cover was high in Tshakhuma village (1.70 ± 0.09 m) and low at Ha Mutsha village (1.03 ± 0.03 m). In all six village focus group discussions, it was noted that mechanical clearing of L. camara was the most used method, but they reported minimum help from the government particularly Working for Water (WfW). The study concludes that L. camara has no substantial adverse impacts to most of the respondents. The study further noted that L. camara is dominant in most household yards ii and that management is taking place however current control options are not enough on their own. Suggestions for further research are to explore more alternative indigenous species present or easily accessible to the community members which may offer the same benefits as IAS. Furthermore, additional research at local level is required for implementing management techniques best suited for the area.
Keywords: Lantana camara -- South Africa -- Vhembe District Municipality; Introduced organisms -- South Africa -- Vhembe District Municipality; Biological invasions -- South Africa -- Vhembe District Municipality; Plant invasions -- South Africa -- Vhembe District Municipality; Lantana camara -- Control -- South Africa -- Vhembe District Municipality; South Africa -- Rural conditions; Ethnoscience -- South Africa -- Vhembe District Municipality